Physiological significance of the KCNQ4-mediated M-current in the pedunculopontine nucleus of the reticular activating system - Stupniki, Sofia (2019)
The pedunculopontine nucleus (PPN) is part of the reticular activating system (RAS) which is associated with sleep regulation. The PPN has cholinergic and non-cholinergic neurons. A hallmark of the PPN-cholinergic neurons is the M-current, a slowly activating, non-inactivating voltage-gated potassium current. KCNQ2 to 5 subunit alone or in combination are responsible for the M-current. Our aim was to investigate the contribution of the KCNQ4 subunit to PPN neuronal function. We used a transgenic mouse model for KCNQ4 (knock-out (KO)) and one with fluorescent-labeled cholinergic neurons (tdTomatoStop+ChAT::Cre). We analyzed KCNQ4 expression by real-time PCR and its localization using immunofluorescence. We also studied the M-current by electrophysiology on brain slices, the contribution of KCNQ4 to neuronal activity and its influence on circadian rhythm. We found a weak mRNA expression of KCNQ4 in PPN and the protein was located only on cholinergic neurons of the external limits of the nucleus. M-current was present in most of cholinergic neurons in WT animals, but absent in 40% of them in the KO ones. These last also exhibited behavioral alterations in the activity cycles showing a 5-hour increase and a higher sensitivity to changes in the light/darkness cycles. In summary, we found that only a subpopulation of PPN cholinergic neurons have KCNQ4-dependent M-current and this subunit contributes to modulate the circadian rhythm through the activity of the RAS system.